The Importance of Anti-Corruption Education in Building a Culture of Integrity in Indonesia - Abdi Saputra Jaya Tumanggor; Rangga Wijaya; Intan Nurina Seftiniara (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This research aims to describe the urgency of anti-corruption education as a preventive measure to prevent acts of corruption, viewed both from the aspects of formal education and public services. This research was conducted using the literature study method. The researcher conducted a literature study with the aim of providing an in-depth understanding of the importance of anti-corruption education and the importance of the value of integrity in society, so that the researcher grouped, processed and used only relevant literature. The research results show that anti-corruption education as an effort to prevent criminal acts of corruption should be carried out as early as possible. In other words, it is very urgent that anti-corruption education be applied to students and every group, including state civil servants as holders and regulators of public interests. In this way, Indonesia's goal as a land of integrity can be fully achieved.